2018
DOI: 10.1021/acsami.7b15127
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Nanosensors for Colorimetric Detection and Dosimetry in Proton Beam Radiotherapy

Abstract: Proton beam therapy (PBT) is a state-of-the-art radiotherapy treatment approach that uses focused proton beams for tumor ablation. A key advantage of this approach over conventional photon radiotherapy (XRT) is the unique dose deposition characteristic of protons, which results in superior healthy tissue sparing. This results in fewer unwanted side effects and improved outcomes for patients. Currently available dosimeters are intrinsic, complex, and expensive and are not routinely used to determine the dose de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Additionally, other configurations for this protein‐based radiation sensor will bring improvements in the function and ease of use of this system. Previous work has shown that gold nanoparticle‐based sensors can be incorporated into a gel, which allows the system to be applied to the surface of the patient rather than in solution, and allows measurement of dose in 3D (S. Inamdar et al, ) (Karthik Pushpavanam et al, ). The protein‐based sensors described here should be able to be extended into the gel system as well through conjugation of the protein to the gel matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, other configurations for this protein‐based radiation sensor will bring improvements in the function and ease of use of this system. Previous work has shown that gold nanoparticle‐based sensors can be incorporated into a gel, which allows the system to be applied to the surface of the patient rather than in solution, and allows measurement of dose in 3D (S. Inamdar et al, ) (Karthik Pushpavanam et al, ). The protein‐based sensors described here should be able to be extended into the gel system as well through conjugation of the protein to the gel matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a gold‐alanine nanocomposite has been evaluated as a radiation dosimeter but the requirement of a sophisticated readout technique like electron paramagnetic resonance has prevented its clinical translation (Guidelli, Ramos, Zaniquelli, Nicolucci, & Baffa, ). To mitigate these concerns, a colorimetric sensor based on the formation of gold nanoparticles as a response to therapeutic levels of ionizing radiation was demonstrated (Sahil Inamdar et al, ; Pushpavanam et al, ). The intensity of color was proportional to the intensity of irradiation and was used as a measure of ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles demonstrate unique size- and shape-dependent plasmonic properties, which have been exploited in several biomedical applications. , We recently developed a sensing approach in which templating ligands (e.g., cationic surfactants) facilitate the formation of gold nanoparticles from colorless precursor salt solutions following exposure to therapeutic levels of radiation. Here, we carried out fundamental studies on the templating of gold nanoparticles by amino acids and related compounds under ionizing radiation. Parallel screening, chemical informatics modeling, foundational mechanistic studies, and translational evaluation were carried out, and lead candidates were formulated as radiation-responsive amino acid nanosensor gels or RANGs for use in dose detection applications.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic nanoparticles, especially gold and silver nanoparticles, have been extensively applied to colorimetric bioanalytical assays for detecting various analytes. They exhibit strong localized surface plasmon resonance (LSPR) as well as characteristic size- and distance-dependent optical absorption properties. , Rege and co-workers recently developed a gel-based colorimetric nanosensor dosimeter for proton radiation . In their assay, proton irradiation triggers the reduction of gold ions to gold nanoparticles within the gel matrix with a detection range of 0–3 Gy.…”
Section: Introductionmentioning
confidence: 99%